El problema del innatismo en Antonio Rosmini : (parte II) - Franck, Juan F. (Sapientia, 2007)
This part of the article reviews the main modern theories on innatism, and assesses the strength and the weakness of each of them from the point of view of the Rosminian theory of the innate presence of the idea of being. It highlights the simplicity of such theory, which confers on it a highly explaining value, in contrast with the difficulties raised by theories like those of Descartes, Locke, Leibniz, Malebranche, and Kant.